Environmental education in libraries – theoretical foundations and practical implementation. Issue 4 (3rd June 2020) - Fedorowicz-Kruszewska, Małgorzata
Abstract : Purpose: The purpose of this paper is to explain the concepts related to environmental education in the context of sustainable development, to indicate the links between them as well as to identify and organize elements of library activities that have the potential to implement environmental education. Design/methodology/approach: The method of analysis and criticism of scientific and professional literature and research reports was used. The multiple case study method was also used. Findings: An analysis of literature and multiple case studies confirms the assumption that sustainable development is now a new paradigm of librarianship. Among the goals of sustainable development are environmental goals, which in libraries can be achieved through environmental education. A broad approach to environmental education has been proposed, which is implemented not only by using library services but also by building green collections, contacts with environmentally involved librarians, using ecological library infrastructure, observing sustainable management methods in libraries, cooperation between the library and the external environment in terms of the natural environment. Research limitations/implications: An analysis of 20 case studies was carried out regarding the implementation of pro-environmental measures in libraries. Examination of a larger number of case studies would probably give a more complete picture of this area of activity in libraries. The next stage of research should be the development of standards/guidelines in the field of environmental education in libraries, and then the development of methods and techniques for assessing the quality of library activities in this area and methods for assessing the impact of libraries on society and the environment in the field of environmental education. Practical implications: The paper indicates – based on case study analyses – those library elements that have potential in the field of environmental education. They were ordered in categories that were assigned to the three main components of a library: people, artefacts and processes. Social implications: Sustainable development is a new library paradigm. The paper focuses on the environmental area, specifically environmental education. It has been recognized that libraries have considerable potential for environmental education and should be seen as socially responsible organizations that take responsibility for the impact of their decisions and actions on society and the environment. Originality/value: The paper explains the basic concepts of environmental education and the relationships between them. It defines the area of environmental education in libraries in terms of library activity elements that can be used to organize them according to the three main components of a library, which are people, artefacts and processes. The paper also indicates that sustainable development should be treated as a new paradigm of librarianship, and environmental education as a new research field of library and information science.